Lattice-matched epitaxial graphene grown on boron nitride - Davies, Andrew; Albar, J.D.; Summerfield, Alex; Thomas, James C.; Cheng, Tin S.; Korolkov, Vladimir V.; Stapleton, Emily; Wrigley, James; Goodey, Nathan L.; Mellor, Christopher J.; Khlobystov, Andrei N.; Watanabe, Kenji; et al. (American Chemical Society, 2018)
Lattice-matched graphene on hexagonal boron nitride is expected to lead to the formation of a band-gap but requires the formation of highly strained material and has not hitherto been realised. We demonstrate that aligned, lattice-matched graphene can be grown by molecular beam epitaxy using substrate temperatures in the range 1600-1710 °C and co-exists with a topologically-modified moiré pattern, and with regions of strained graphene which have giant moiré periods up to ~80 nm. Raman spectra reveal narrow red-shifted peaks due to isotropic strain, while the giant moiré patterns result in complex splitting of Raman peaks due to strain variations across the moiré unit cell. The lattice-matched graphene has a lower conductance than both the Frenkel-Kontorova-type domain walls, and also the topological defects where they terminate. We relate these results to theoretical models of band-gap formation in graphene/boron nitride heterostructures.